PENGEMBANGAN KAMUS SAKU ARAB - INDONESIA UNTUK MENINGKATKAN KETERAMPILAN MENULIS BAHASA ARAB KELAS VIII DI MTS MA’ARIF 1 JOMBANG - Rahmawati, Rina Dian; Khamim, Muhamad (JoEMS (Journal of Education and Management Studies), 2021)
This study aims to produce a product in the form of an Arabic-Indonesian Pocket Dictionary for class VIII MTs Ma'arif 1 Jombang as a support for the use of textbooks. Equipped with Mufrodat, Qiroah, 'Ibarot and Qowa'id. The research model used is the Research and Development model. Data collection methods were in the form of pre-test, post-test and questionnaire using research instruments in the form of validation sheets, assessment sheets, and student response sheets on small-scale trials and large-scale trials. The results of this study are (1) has succeeded in developing a Pocket Arabic-Indonesian dictionary product for class VIII MTs Ma'arif 1 Jombang, (2) based on the assessment of experts consisting of material experts, media experts, this dictionary has very good quality ( SB), (3) based on the small-scale trial, the student's response to the developed product was agree (S) and in the large-scale trial the student's response to the Arabic-Indonesian dictionary for class VIII MTs Ma'arif 1 Jombang was strongly agree. (SS), based on the results of field tests, student responses to the product developed were categorized as strongly agree (SS). This shows that they strongly agree that the Arabic-Indonesian pocket dictionary can improve Arabic writing skills for class VIII at MTs Ma'arif 1 Jombang.